Profil Prokrastinasi Akademik Siswa SMK Negeri di Kota Serang - Fisca Fitri Agustina; Rahmawati Rahmawati; Deasy Yunika Khairun (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2023)
This study aims to find out the general description of academic procrastination in State Vocational School students in Serang City. The type of research used was a descriptive study with a sampling technique using proportional random sampling with a total sample of 336 students in Serang City, divided into 8 schools. The measurement tool used is the academic procrastination scale which consists of aspects, namely delays in starting or completing the tasks at hand, delays in doing assignments, time gaps between plans and actual performance and carrying out other activities that are more enjoyable, which as a whole consists of 37 statement items . The data analysis technique uses a quantitative descriptive method. The results of the study showed that the level of academic procrastination in students in the high category was 3.1%, medium was 89%, and low was 7.1%. Therefore, the academic procrastination of State Vocational High School students in Serang City is in the moderate category. After analyzing the results of the research and obtaining categorization, the guidance and counseling program design was made based on the needs of the student.